The Assessment of Adolescent Girls' Menstrual Hygiene Knowledge and Practice in Ede South Local Government Secondary Schools, Ede, Osun State (Fountain Journal of Natural and Applied Sciences, 2023)
The onset of menstruation denotes a landmark event in the pubertal development of the adolescent girl. Adolescent girls should have adequate knowledge of menstrual hygiene before menarche. Lack of adequate knowledge and good menstrual hygiene practices can have far-reaching consequences for a girl's well-being, dignity, reproductive health, and sexual health. Hygiene-related practices during menstruation are of considerable importance. This study assessed the knowledge and Practice of menstrual hygiene among adolescent girls in Ede South local government secondary schools, Ede, Osun State. This study adopted a descriptive cross-sectional study design. The study population was adolescent girls between the ages of 10 and 19 who have attained menarche, using multi-stage sampling as the sampling technique. A structured questionnaire comprising three sections was used to elicit information from the respondents. The data were analysed using Statistical Package for Social Sciences (SPSS) version 20. The result showed that the majority (62.6%) of the respondents were between 16 and 18 years old and had attained menarche at 13. Most respondents had heard about menstruation before menarche (85.0%), and mothers (79.1%) were the primary source of information. Most (89.70%) respondents had good knowledge of menstrual hygiene. Also, most (53.0%) respondents had good menstrual hygiene practices. In the test for the hypothesis, there is a significant association between sociodemographic characteristics such as tribe, class, age at menarche, and the Practice of menstrual hygiene. There is also a significant relationship between knowledge and Practice of menstrual hygiene (p = 0.017). This study concluded that the majority of the respondents had good knowledge as well as good practice regarding menstrual hygiene. Keywords: Menstrual Hygiene, Adolescents, Knowledge, Practice
Keywords: Menstrual hygiene, adolescents, knowledge, practice.